The mediating role of interactive media on the relationship of LGU-run museum attributes to visit and re-visit intention - Kelvin Carl M. Otilla; Jehan R. Nepomuceno; Jamuel J. Neo; Honesto O. Camino (Borneo Novelty Publishing, 2026)
Purpose – This study aims to examine the role of local government unit (LGU)-run museums in fostering community identity and cultural preservation, and to analyse how museum characteristics influence Generation Z visitors’ intention to visit and revisit, particularly through the lens of Uses and Gratification Theory.Design/Methodology/Approach – The study employs a quantitative approach using path analysis to explore the relationships between museum attributes and visitor intentions. A cross-sectional survey design with Likert-scale instruments was used to collect data, with a particular focus on the mediating role of interactive media features.Findings – The findings indicate that interactive media features play a significant, though limited, mediating role in influencing the relationship between museum characteristics and Generation Z’s visitation and revisit intentions. While interactive elements enhance engagement, their impact does not fully compensate for other underlying museum qualities.Originality/Value – This study provides valuable insights into the evolving expectations of younger audiences in the context of cultural institutions, highlighting the need for LGU-run museums to strategically integrate digital and interactive experiences. It contributes to the literature by emphasizing a balanced approach that aligns technological innovation with the core objectives of cultural preservation and community engagement.